(untitled) (African Journal of Fisheries Science, 2013)
Growth, feed utilization, and economic limit of commercial pelleted feed use were compared between daily-fed and feed deprived groups of Clarias gariepinus (Burchell, 1822) raised under low density culture. Groups of C. gariepinus were fed daily (Treatment 1) or on alternate days (Treatment 2) for 5½ months, with 45% crude protein commercial pellets. Feeding was at a rate of 6% body weight per day which was considered satiation feeding. Cost and revenue were determined on the basis of feed cost and revenue from fish sales respectively. Treatment 1 yielded profits up to a mean weight of 64±8 g at feed conversion ratio 1.0±0.08 and 4.71% loss at mean weight of 105±10 g and feed conversion ratio (FCR) 2.1±0.7. Treatment 2 was profitable up to harvest mean weight of 264±10 g. Feed conversion ratio, mean weight, and total weight, were significantly higher in Treatment 1 (p<0.05). Cost-benefit ratio and percentage profit were significantly higher in Treatment 2 (p<0.0001). Thus the economic limits were 2 months at mean weight of 105±10 g; and 5 months at mean weight 264±10 g; in Treatments 1 and 2 respectively. The skip-a-day feeding strategy adopted in Treatment 2 was effective in extending the economic limit of conventional feeding using commercial pelleted feed in low density commercial catfish culture. The limits established in this study could serve as an advisory to farmers on the appropriate time to switch from the expensive commercial pelleted feeds usually fed at the early stage of grow-out to farm-made feeds.